Effect of Morning Walking on the Hemoglobin Levels of Adolescents with Anemia - Elma Nurfu’adina Sukarman; Linda Amalia; Afianti Sulastri (Universitas Negeri Semarang, 2025)
Anemia is a global health problem that affects the physical fitness, cognitive function, and academic performance of adolescents. In Indonesia, the prevalence of anemia in adolescents is still relatively high. One of the factors contributing to this condition is the lack of physical activity that could potentially support the increase of hemoglobin levels. This study aims to observe if there is a significant effect of morning walking activity on the hemoglobin levels of adolescents with anemia at Al-Amanah Cileunyi Junior High School. This study used quantitative methods with a quasi-experimental approach and a one-group pre-test and post-test design. A sample of 30 people was selected using a purposive sampling technique from a population of 57 students in class VIII based on inclusion and exclusion criteria. Interventions in the form of morning walking activities were held twice a week for three weeks. Measurement of hemoglobin levels was collected before and after the intervention using the EasyTouch GCHb digital device. Data analysis used the Wilcoxon signed-rank test and the Mann-Whitney U test. There was a significant increase in hemoglobin levels after the intervention (P < 0.05), and there was a significant difference between male and female. Morning walking has a positive effect on increasing the hemoglobin level of adolescents with anemia. It is recommended that this activity be implemented as a promotive and preventive strategy in the school environment.